2020
DOI: 10.3390/molecules25173834
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated LPS/GalN-Induced Liver Injury in the Stress-Sensitive Wistar Kyoto Rat Is Associated with Changes in the Endocannabinoid System

Abstract: Acute liver injury (ALI) is a highly destructive and potentially life-threatening condition, exacerbated by physical and psychological stress. The endocannabinoid system plays a key role in modulating stress and hepatic function. The aim of this study was to examine the development of acute liver injury in the genetically susceptible stress-sensitive Wistar-Kyoto (WKY) rat compared with normo-stress-sensitive Sprague Dawley (SD) rats, and associated changes in the endocannabinoid system. Administration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Cumulatively, CB2 activation could mitigate GalN/ LPS-induced ALF by mediating the M1 to M2 transition in macrophages and modulating miR-145 expression to hamper TLR4 signaling following LPS-triggered inflammation. Killilea et al (2020) showed that pretreatment with low-dose JWH133 did not attenuate LPS/GalN-induced ALI in Sprague-Dawley or WKY rats at 6 h. These results indicated a lack of CB receptor-mediated protection in ALI SD or WKY rats, and protective effects could be noted with higher doses of JWH133 over different time intervals (e.g., 24 h) after prolonged administration. Further studies are needed to determine whether CB2R activation stimulates or mitigates severe liver injury in stress-sensitive rats.…”
Section: Acute Liver Failurementioning
confidence: 87%
“…Cumulatively, CB2 activation could mitigate GalN/ LPS-induced ALF by mediating the M1 to M2 transition in macrophages and modulating miR-145 expression to hamper TLR4 signaling following LPS-triggered inflammation. Killilea et al (2020) showed that pretreatment with low-dose JWH133 did not attenuate LPS/GalN-induced ALI in Sprague-Dawley or WKY rats at 6 h. These results indicated a lack of CB receptor-mediated protection in ALI SD or WKY rats, and protective effects could be noted with higher doses of JWH133 over different time intervals (e.g., 24 h) after prolonged administration. Further studies are needed to determine whether CB2R activation stimulates or mitigates severe liver injury in stress-sensitive rats.…”
Section: Acute Liver Failurementioning
confidence: 87%
“…Mice lacking the CB1 receptor in the liver have significantly less hepatic steatosis, hyperglycemia, and dyslipidemia during over-nutrition [100], highlighting an important role for the CB1 receptor in regulating normal hepatic metabolism. Selective studies of the endocannabinoid system in the context of liver diseases are showed in Table 3 [106][107][108][109][110][111][116][117][118][119][120][121][122][123][124].…”
Section: Rock1 Mediates Endocannabinoid-induced Lipogenesismentioning
confidence: 99%